How to speak, how to listen - Adler, Mortimer Jerome, 1902-2001. (New York : Simon & Schuster, 1997)
Gives the reader a short course in effective communication filled with the Adler wisdom and wit.
The untaught skills -- The solitary and the social -- "That's just rhetoric!" -- The "sales talk" and other forms of persuasive speech -- Lectures and other forms of instructive speech -- Preparing and delivering a speech -- With the mind's ear -- Writing while and after listening -- Question and answer sessions : forums -- The variety of conversations -- How to make conversation profitable and pleasurable -- The meeting of minds -- Seminars : teaching and learning by discussion -- Conversation in human life.
Companion vol. to: How to read a book.
Keywords: Oral communication -- Popular works; Popular works